Enhanced Hydrogen Evolution Activity of Phosphorus‐Rich Tungsten Phosphide by Cobalt Doping: A Comprehensive Study of the Active Sites and Electronic Structure. Issue 9 (4th May 2021) - Yang, Yixuan; Feng, Xiaoyu; Liu, Zhizhong; Zhang, Xuming; Song, Hao; Pi, Chaoran; Gao, Biao; K Chu, Paul; Huo, Kaifu
Abstract: Phosphorus‐rich transition metal phosphides (TMPs) are considered efficient electrocatalysts for the hydrogen evolution reaction (HER). However, the actual activity of P‐rich TMPs is not as good as expected because of the undesirable electronic structure. Transition metal doping has been shown to be effective in improving the HER activity of TMPs in both acid and alkaline media, but the underlying mechanism is ambiguous, especially for P‐rich TMPs. Herein, cobalt‐doped and phosphorus‐rich tungsten phosphide nanowire arrays (Co/WP2 NWs/CC) are synthesized and the electrochemical properties and mechanism are determined by both experiments and theoretical calculation. The results reveal that Co dopants serve as inert catalytic sites and do not participate in HER process, but the Co/WP2 NWs/CC exhibits enhanced electrocatalytic activity as a result of the lower water dissociation barrier and hydrogen adsorption/desorption free energy on W or P sites and improved conductivity by strong electron‐donating effects of Co dopants, thereby boosting the catalytic activity and kinetics. Abstract : Inert yet effective : The excellent hydrogen evolution reaction (HER) activity of Co‐doped WP2 is revealed by both experimental and DFT studies. The results demonstrate that Co dopants with inert activity can largely improve the intrinsic activity of WP2 through lowering the water dissociation barrier and hydrogen adsorption/desorption free energy and improving whole conductivity by strong electron‐donor effect of Co dopants.